APPLICATION OF DATA MINING TO PREDICT STOCK INVENTORY IN RAGIL MART SHOP USING MULTIPLE LINEAR REGRESSION METHODS - Nur Cahyono; Ngajiyanto Ngajiyanto; Supriyanto Supriyanto (LPPM STMIK Pringsewu, 2023)
Along with the development of information technology, the need for fast, accurate and relevant information is increasing. The need for accurate information is needed in everyday life, so that information will be an important element in the development of society today and in the future. . Often this information still has to be extracted from data with a very large population. The Ragil Mart store provides goods for the basic needs of the community, namely goods that concern the lives of many people with a high scale of meeting needs and are a supporting factor for people's welfare. the concept of implementing data mining that is used to assist the store in determining stock availability which is expected to be able to provide the best results so that the risk of errors in providing stock is small. In the grouping process, a method is used, namely the method.